Peningkatan Kesiapan Literasi Digital Dalam Menunjang MBKM Kampus Mengajar di Wilayah Desa Tajur Halang SD, SMP Sinar Kasih dan Masyarakat Sekitar - Soenandi, Iwan Aang; Angin, Prasasti Perangin; Anu, Benisius (Jurnal Pengabdian kepada Masyarakat UBJ, 2021)
Digital learning is a necessity in the industrial era 4.0. Students must be equipped with various skills based on information technology. Digital learning infrastructure and the ability of Human Resources (HR) for SD and SMP Sinar Kasih need attention in creating schools based on digital learning. In addition, the people of Kampung Cina where the Sinar Kasih Elementary and Middle School are located have the same needs, where the students who attend school there are free of charge for the school fees, because their vision is to serve the underprivileged communities around the Tajurhalang neighborhood and village. Problem solving is carried out through training to increase the capacity of SD and SMP Sinar Kasih human resources to carry out digital learning. The material presented is divided into two, namely creative pedagogy and digital literacy. Second, through the fulfillment of digital learning equipment, including the provision of computers, LCD projectors, training modules, increasing internet capacity, and providing video tutorials for teachers and students. This will also support the effectiveness of the implementation of the Independent Learning Campus Merdeka BKP Teaching Assistance which has been carried out by 25 Ukrida students in Sinar Kasih Elementary and Middle School.